Old residual mortar as a quality indicator of recycled brick aggregate - Md Roknuzzaman; NHM Kamrujjaman Serker; Md Mahabub Rahman (Sustainable Structures)
Old residual mortar (RM) on recycled aggregate surfaces is a major factor contributing to its lower quality. The present study aims to quantify the effect of old mortar on the properties of recycled brick aggregates (RBA) and recycled concrete (ReC) made with them. The process involves collecting and crushing discarded concrete blocks from seven sources to create recycled brick aggregates. A chemical-thermal combined process removes old mortar, and with varying RM contents, the aggregate properties are determined. C-25-grade concrete specimens are prepared using RBA with different RM content and tested for workability, compressive strength, splitting tensile strength, flexural strength, water absorption, bulk density, and voids in hardened concrete. Regression models expressing the change in properties with RM content are presented. The study reveals that the quality of RBA and concrete worsens with increasing RM, with a 20% RM value being considered a limiting value to maintain minimal variation in properties. The regression models suggest that every 10% increase in RM may result in an 11% increase in water absorption of RBA, an 8% increase in aggregate crushing value (ACV), a 3.6% increase in Los Angeles (LA) value, a 10% loss in compressive strength of ReC, a 7% loss in tensile strength, and a 9% loss in flexural strength, approximately. The developed models may be used to predict the expected quality of RBA and ReC based on their attached old RM, which would be helpful in deciding their usage for different applications.